919 Surgical Voice Restoration – Improving Out of Hours Management: A Multidisciplinary Quality Improvement Project. (12th October 2021) - Wallace, J; McCord, J; Roberts, B; Browning, S
Abstract: Aim: Swansea Bay University Health Board have a caseload of 37 surgical voice restoration (SVR) laryngectomies. These patients are excellently managed during working hours, by a SALT-led service. Concerns were raised regarding the quality of out of hours management: the aim of this project was to identify and address the factors contributing to the difference in care received. Method: A questionnaire was sent to current junior doctors to assess knowledge and confidence when managing SVR patients. Phone interviews were conducted with SVR patients to discuss the issues from a patient's perspective. The junior doctor team and SALT team liaised to identify contributing logistical issues. Results: The junior doctor survey indicated both experience and confidence were low, including amongst senior trainees. 58.3% were unfamiliar with equipment used to change a speech valve. Patient interviews revealed several issues, such as delays to treatment and unnecessary admissions. Logistical concerns included inability to access equipment out of hours and an absence of departmental guidelines. Conclusions: This project demonstrates a collaborative approach between junior doctors and SALT, to improve the quality of care for a sub-set of patients with highly specialised needs. We identified the contributing factors for the disparity in services and tailored interventions to provide the junior doctors responsible for out of hours care, with the knowledge and skills to provide a better standard of care.